Evaluation‏ ‏the Properties of Mortar Containing Plastic Boxes Waste (Journal of University of Babylon for Engineering Sciences, 2023)
Countries generate vast numbers of plastic boxes waste used to hold fruits and vegetables. When the waste resulting from this type of plastic is discarded, it threatens the environment. This work studied the utilization of this type of waste to produce green cementitious materials. The influence of Plastic Boxes Waste (PBW) on the characteristics of mortar is presented. The PBW was utilized as particles which was used as a replacement for fine aggregate. In addition to the reference mixture, ten mixtures containing different volumetric percentages of PBW particles as replacement of sand volume (10, 20, 30, 40, 50, 60, 70, 80, 90-100%) were prepared. The effect of PBW particles on the mortar properties were evaluated by measuring slump flow, density, compressive, flexural, and splitting tensile strengths. The results show that there is a possibility of producing cement mortar containing high quantity of PBW, resulting in lightweight and ultra-lightweight mortar with a density less than 1200 kg/m3. Additionally, the possibility of producing normal weight concrete mortar having a strength of 20 MPa using waste plastic boxes (PBW) particles is well established with a substitution ratio of up to 20%, and obtaining light weight concrete mortar having a strength of about 10 MPa using PBW particles with a substitution ratio of 60%.